Oracle database 11g release 2 high availability [ maximize your availability with grid infrastructure, Oracle real application clusters, and Oracle data guard - Jesse, Scott; Burton, William , 1948-; Vongray, Bryan (McGraw-Hill, 2011)
Provides information on using Oracle database 11g to grid-enable an IT framework, maintain databases, build test clusters, and identify and undo user errors